Trapped in the Digital World: Influence Social Media Addiction Leads to Body Dissatisfaction - Asiah; Erwita Ika Violina; Rafael Lisinus Ginting; Kamila Huwaida (Bisma The Journal of Counseling, 2025)
Social media has evolved into a fundamental component of daily life, influencing nearly every aspect of social interaction, entertainment, and communication. However, excessive engagement with social media can impact mental health, particularly in relation to body image perception. The purpose of this study is to evaluate the extent to which social media addiction influences body image among college students. The methodology used is descriptive, with a descriptive correlation study design, aiming to explain the relationship between social media addiction and body dissatisfaction among college students. The study population consisted of 157 college students, with the sample size calculated using the Slovin formula, resulting in 112 respondents. Sample recruitment was conducted through simple random sampling to ensure respondent diversity. The instruments used in this study were the social media addiction scale and the body dissatisfaction scale. The collected data were analyzed using simple linear regression tests. Prior to this, prerequisite tests were conducted, particularly the normality test, which yielded a value of 0.200, indicating normally distributed data, and the linearity test, which yielded a significance value of 0.000, indicating a highly significant linear relationship. The results of the simple linear regression showed a value of 0.325, indicating a weak positive correlation between social media addiction and body dissatisfaction. These findings suggest that social media addiction influences body dissatisfaction, although the effect is relatively modest.